Potential for Agropolitan Area Development Through Agribusiness-Based Development in Dwi Tiro Village, Bontotiro District, Bulukumba Regency, South Sulawesi Province, Indonesia - Irfa Dewi Anugrah; Hasaruddin Hasaruddin; Asni Djamereng (Glosains: Jurnal Sains Global Indonesia, 2026)
Background:  Most of the people of Dwi Tiro Village, South Sulawesi Province, Indonesia had a livelihood as farmers, which causes the area to have great potential in its agricultural sector but the ongoing problems of development inequality hinder this potential. Objective: The development of agropolitan areas in this region represents the most appropriate government effort to accelerate development. Using a qualitative case study approach with observation, interviews, and documentation, this study aims to analyze the potential of agropolitan areas through agribusiness-based development in Dwi Tiro Village by examining the forms and strategies of agropolitan area development. Methods: This study uses a qualitative approach with a case study design to analyze in depth the potential and development of agropolitan areas based on agribusiness systems in Dwi Tiro Village, Bontotiro District, Bulukumba Regency, South Sulawesi. Results: The results of this study show that the development of agropolitan areas in Dwi Tiro Village is carried out with several strategies: namely village deliberation before determining the program, strengthening institutions and capacity of agribusiness actors and providing infrastructure and supporting facilities for agribusiness. Furthermore, the form of agropolitan area development includes several things, namely development based on superior potentials and commodities, integrated development of agricultural and livestock businesses and finally strengthening institutions and supporting facilities. Conclusion: This study is expected to serve as a guide for village governments in developing agropolitan areas founded on superior local potential and agribusiness-based development, and as a reference for strengthening institutions and supporting facilities to sustain agribusiness activities.